The Relationship Between Uric Acid Levels and Hypertension in Prolanis Patients at the Singandaru Public Health Center, Serang City - Al Fina Nurhidayah; Syarah Anliza; Adipura Atmadja Egok; Dewi Maria Yuliani; Liu Zhi hong (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2025)
Abstract Hypertension is a chronic disease with a continuously increasing prevalence in Indonesia, including in Serang City. One of the contributing risk factors for hypertension is high uric acid levels (hyperuricemia). An imbalance in the production and excretion of uric acid can lead to its accumulation in the blood, which in turn triggers an increase in blood pressure. The Prolanis (Chronic Disease Management Program) at Public Health Centers aims to manage chronic illnesses like hypertension in a more integrated manner. This study aimed to determine the relationship between uric acid levels and the incidence of hypertension in Prolanis patients at the Singandaru Public Health Center, Serang City. This was an analytical study with a cross-sectional design. The study population consisted of 92 Prolanis patients, from which a sample of 50 patients was taken. The results of the bivariate analysis of the two variables using the Chi-Square Test yielded a p-value of 0.000 (p < 0.05), which indicates a significant relationship between uric acid levels and hypertension in Prolanis patients. Thus, it can be concluded that there is a significant relationship between uric acid levels and hypertension in Prolanis patients at the Singandaru Public Health Center, Serang City.